2008
DOI: 10.1007/978-3-540-69387-1_43
|View full text |Cite
|
Sign up to set email alerts
|

Design of Optimal Laser Fields to Control Vibrational Excitations in Carboxy-myoglobin

Abstract: Abstract. Optimal control theory is applied to obtain infrared laser pulses for the selective vibrational excitation of a two mathematical dimensional model of carboxy-myoglobin. Density functional theory is used to obtain the potential energy and dipole moment surfaces of the active site model. The Conjugate gradient method is employed to optimize the cost functional and to obtain the optimized laser pulses. Optimized laser fields are found which give virtually 100% excitation probability to preselected vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Joffre and co-workers, 48 in their pump-probe studies, demonstrated coherent vibrational ladder climbing up to the v = 6 state of the CO vibration in carboxy-heomoglobin by means of midinfrared laser pulses. 51,52 Recently, Gollub et al 53 performed theoretical studies on the vibrational ladder climbing in the transition metal carbonyl complex, MnBr͑CO͒ 5 ͑having similar characteristics to the CO-heme complex͒. Quantum wave packet studies performed by Kühn on CO-heme compounds 50 demonstrated that even if the initial average energy of CO-stretch is above the dissociation limit, there is only a small probability of dissociation of the Fe-CO bond.…”
Section: Introductionmentioning
confidence: 99%
“…Joffre and co-workers, 48 in their pump-probe studies, demonstrated coherent vibrational ladder climbing up to the v = 6 state of the CO vibration in carboxy-heomoglobin by means of midinfrared laser pulses. 51,52 Recently, Gollub et al 53 performed theoretical studies on the vibrational ladder climbing in the transition metal carbonyl complex, MnBr͑CO͒ 5 ͑having similar characteristics to the CO-heme complex͒. Quantum wave packet studies performed by Kühn on CO-heme compounds 50 demonstrated that even if the initial average energy of CO-stretch is above the dissociation limit, there is only a small probability of dissociation of the Fe-CO bond.…”
Section: Introductionmentioning
confidence: 99%
“…The application of optimal control theory, in a theoretical context, requires knowledge of the quantum mechanical behaviour of the system during its interaction with a laser pulse. This approach [8,9] has not previously been applied to an enzyme reaction.…”
Section: Introductionmentioning
confidence: 98%
“…Hemoproteins are the most studied proteins and play numerous important physiological roles, such as transportation and storage of oxygen. The structure and binding energies of ligands, such as O 2 , CO, and NO binding with the hemoproteins, have been investigated both experimentally and theoretically. The pump–probe studies performed by Joffre and co-workers demonstrated, by the means of mid-infrared laser pulses, coherent vibrational ladder climbing up to the ν = 6 state of the CO vibration in carboxyhemoglobin (HbCO) . Kühn, in quantum wave packet studies on CO–heme compounds, demonstrated that even if the average initial energy of CO stretch is above the dissociation limit, it is small for the probability of dissociation of the Fe–CO bond .…”
Section: Introductionmentioning
confidence: 99%